A Systematic Literature Review: Business Feasibility Analysis Using Net Present Value (NPV) and Internal Rate of Return (IRR) Methods in the Automotive Industry - Pranoto, Adi; Hermawan, Hery; Albart, Nicko (Jurnal Indonesia Sosial Sains, 2025)
This research evaluates business feasibility in the manufacturing sector using the Net Present Value (NPV) and Internal Rate of Return (IRR) methods. Both of these methods are financial analysis tools that play an important role in making investment decisions, especially in projects that require large capital investments and face market uncertainty. The NPV method assesses the potential profit of a project based on the time value of money, while the IRR identifies the minimum rate of return required for the investment to be viable. This study uses the Systematic Literature Review (SLR) approach to compile and analyze various studies that discuss the application of NPV and IRR in the manufacturing industry. By comprehensively understanding the application of these two methods, it is hoped that manufacturing companies can conduct more accurate investment assessments and maximize the sustainability of business projects.